Fibroid explants reveal a higher sensitivity against MDM2-inhibitor nutlin-3 than matching myometrium - Markowski, Dominique Nadine; Helmke, Burkhard Maria; Radtke, Arlo (BMC women's health, 2012)
Spontaneous cessation of growth is a frequent finding in uterine fibroids. Increasing evidence suggests an important role of cellular senescence in this growth control. Deciphering the underlying mechanisms of growth control that can be expected not only to shed light on the biology of the tumors but also to identify novel therapeutic targets.
Gesehen am 04.10.2018